PENGARUH PENGGUNAAN POP-UP BOOK TERHADAP KEMAMPUAN MENGENAL KONSEP BILANGAN ANAK USIA 4-5 TAHUN DI TK TUNAS MELATI KANDIS, KABUPATEN SIAK - Vioro Nauli; Daviq Chairilsyah; Devi Risma (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Based on the results of field observation on the ability to recognize the concept of the number of students has not developed optimally. So it is necessary to apply the use of pop-up book. This study aims to determine the effect of the use of pop-up book on the ability to recognize the concept of the number of children aged 4-5 years in TK Tunas Melati Kandis, Siak District. The sample used in this study were 17 students. The data collection techniques used are observation and documentation. Data analysis technique used t-test with SPSS 20.0. Research hypothesis is the activity of the use of pop-up book has an influence to the ability to recognize the concept of the number of children aged 4-5 years in kindergarten Tunas Melati Kandis. This can be known from the analysis of data obtained thitung = 15.550 and Sig. (2-tailed) = 0.000. Because Sig. (2-tailed) = 0.000 <0,05 it can be concluded that there is a difference in the ability to recognize the concept of significant number of students after the use of pop-up book in learning. So it means Ho is rejected and Ha accepted which means there is a very significant difference between before and after doing experiments by applying the use of pop-up book. The influence of the use of pop-up book on the ability to recognize the concept of the number of children aged 4-5 years in TK Tunas Melati Kandis, Siak regency of 58.06%.Keywords: Ability to Know the Concept of Numbers, Use of Pop-Up Book